Planning Your Health: An Assessment of Lifestyle Factors Influencing Creativity of Secondary School Teachers in Alimosho Local Government (UNIZIK Journal of Educational Management and Policy, 2024)
In today’s rapidly changing educational landscape, creativity is not merely a desirable trait but a necessity. The ability to think outside the box allows teachers to address diverse student needs, integrate technology effectively, and navigate the complexities of modern education systems. This study investigates the influence of nutritional health and physical fitness and exercise on the creativity of senior secondary school teachers in Alimosho Local Government, Lagos State, Nigeria. Using a descriptive survey research design, 321 respondents were sampled from a population of 4000 teachers. Data were collected through structured questionnaires and analyzed using linear regression. The results revealed that nutritional health significantly influences creativity (R² = 0.181, β = 0.425, p < 0.05), explaining 18.1% of the variance in creativity. Similarly, physical fitness and exercise significantly influence creativity (R² = 0.143, β = 0.378, p < 0.05), explaining 14.3% of the variance in creativity. Based on these findings, this study concluded that both nutritional health and physical fitness and exercise are critical factors for promoting the creativity of teachers. It, therefore, recommended that educational authorities implement systematic programmes promoting healthy eating and regular physical activity to improve teachers’ creativity and overall well-being.
Keywords: Creativity, exercise, nutritional health, physical fitness, teachers